IL-37 attenuated HPV induced inflammation of oral epithelial cells via inhibiting PI3K/AKT/mTOR - Yahong Shi; Ning Liu; Yunfang Bai; Kunshan Li; Chencong Li; Yujiao Hou (Virology Journal)
Abstract Human papillomavirus (HPV) is the most prevalent sexually transmitted infection globally, with significant implications for various anogenital cancers, such as vulval, vaginal, anal, penile, head and neck cancers. HPV infections have been linked to the induction of inflammation. In contrast, Interleukin-37 (IL-37) is recognized as an anti-inflammatory cytokine. In this study, two distinct types of oral epithelial cells were employed to investigate the impact of HPV on inflammation. The experimental outcomes unequivocally demonstrated that human papillomavirus (HPV) elicited a pronounced and statistically significant induction of inflammatory responses within both varieties of oral epithelial cells under investigation. Interestingly, IL-37 exhibited a mitigating effect, attenuating the HPV-induced inflammation in oral epithelial cells. Further exploration into the molecular mechanisms involved revealed that knockdown (KD) of PI3K compromised the anti-inflammatory effects of IL-37 in response to HPV. Similarly, KD of AKT was found to compromise the regulatory effects of IL-37 on HPV-induced inflammation. Notably, KD of mTOR was identified as a key factor, compromising the anti-inflammatory effects of IL-37 in the context of HPV-induced inflammation. Additionally, the study uncovered that the mTOR inhibitor, rapamycin, could effectively compromise the effects of IL-37 on HPV-induced inflammation. These findings contribute valuable insights into the intricate pathogenesis of HPV-induced inflammation and may pave the way for the development of innovative treatments for this condition.